2019
DOI: 10.3390/ma12111811
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Silica-Based Fillers on the Properties of Epoxy Molding Compounds

Abstract: Global design and manufacturing of the materials with superb properties remain one of the greatest challenges on the market. The future progress is orientated towards researches into the material development for the production of composites of better mechanical properties to the existing materials. In the field of advanced composites, epoxy molding compounds (EMCs) have attained dominance among the common materials due to their excellent properties that can be altered by adding different fillers. One of the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…On the other hand, the following examples are representative of many (probably the majority of) reports which suggest that T g is essentially independent of the filler content in epoxy composites. Linec and Music [29] investigated the effects of the addition of silica of different shape, specific surface area and chemical structure, including crystalline and fused silica, in epoxy moulding compounds and found that T g remained almost constant. Dorigato and Pegoretti [30] introduced both carbon black (CB) and carbon nanofibers (NF) into an epoxy matrix with in situ generated silver nanoparticles and concluded that T g was "slightly reduced"; for example, for 4 wt.% nanofiller the reduction was about 5.5 • C for the CB nanofiller, but only about 2.6 • C for NF.…”
Section: Epoxy Compositesmentioning
confidence: 99%
“…On the other hand, the following examples are representative of many (probably the majority of) reports which suggest that T g is essentially independent of the filler content in epoxy composites. Linec and Music [29] investigated the effects of the addition of silica of different shape, specific surface area and chemical structure, including crystalline and fused silica, in epoxy moulding compounds and found that T g remained almost constant. Dorigato and Pegoretti [30] introduced both carbon black (CB) and carbon nanofibers (NF) into an epoxy matrix with in situ generated silver nanoparticles and concluded that T g was "slightly reduced"; for example, for 4 wt.% nanofiller the reduction was about 5.5 • C for the CB nanofiller, but only about 2.6 • C for NF.…”
Section: Epoxy Compositesmentioning
confidence: 99%
“…Thus, they are widely used as a reinforcement for the plastic industry. In addition, glass beads can be easily and uniformly dispersed throughout the plastic compound and produce smoother flowing compound than with irregular particles [9,10], which ensures that all parts of the electronics are covered with EMC and no short-shot happens even though the filler content is high. In order to improve the bonding between fillers and matrix, the surface of fillers is usually coated with some functional silane as a coupling agent.…”
Section: Introductionmentioning
confidence: 99%
“…The main exothermic transition appeared in the temperature range of approximately 150–220 °C, due to the addition reactions between the epoxy ring and amines of the hardener, side reactions such as etherification of hydroxyl groups and epoxy groups, homopolymerization of epoxy ring opening, and thermal decomposition of weak bonds, occurred in the high-temperature region [ 6 , 46 ]. These transitions became blunt followed by reduced height of the exothermic peak for epoxy composites than that in control epoxy, implying the affluence of initiation of curing reaction in the epoxy composites by silica particles bearing surface –OH groups [ 47 ]. The inflection point temperature of this exothermic peak was considered as T g [ 6 ].…”
Section: Resultsmentioning
confidence: 99%